Enhancement of Gene Editing and Base Editing with Therapeutic Ribonucleoproteins through In Vivo Delivery Based on Absorptive Silica Nanoconstruct (Adv. Healthcare Mater. 4/2023). Issue 4 (6th February 2023) - Kim, Seongchan; Jeong, You Kyeong; Cho, Chang Sik; Lee, SeokHoon; Sohn, Chang Ho; Kim, Jeong Hun; Jeong, Youngdo; Jo, Dong Hyun; Bae, Sangsu; Lee, Hyojin
Abstract : Genome Editing In article 2201825, Dong Hyun Jo, Sangsu Bae, Hyojin Lee and co‐workers develop a novel ribonucleoprotein (RNP) delivery platform, including Cas9 nuclease and base editor, via spongelike structured nanomaterials. This platform increases the delivery efficacy of RNPs in various cells and organs with different genes, and enhances the therapeutic efficiency for tumors, which enables a modular means of in vivo genome editing and other therapeutic purposes.